Rancang Bangun Sistem Informasi Rental Mobil Bebasis Web (Studi Kasus: Zelta Rent Car) - Yuli Fitrisia; Rade Oktari Sakti (Politeknik Caltex Riau, 2022)
Zelta Rent Car is one of the car rentals engaged in car rental services that has a center and branch by providing information through one customer to another, it turns out that this method is less effective because the manager cannot provide complete information about the car being rented and does not there is a notification of the departure schedule so that the customer forgets the departure from the center or branch. Based on the problems of this research, a web-based car rental information system and an integrated SMS gateway were built, both from the center and branches using the RestfullApi webservice.Â This system was built using the prototyping method to make it easier for users to get an overview of the applications created. The purpose of this application also became solution to make it easier for customers to obtain car information and departure notifications that can assist in ordering cars that are integrated with each other from the center or branches. Based on testing Blackbox testing and User Acceptance Testing (UAT) can be concluded that the functional requirements of the system are running well. Applications can provide complete information about rented cars and make it easier for customers because of the notification of the departure schedule.